Green Marketing Strategy and Brand Image: Building Consumer Loyalty for Unilever in Sekip, Medan - Christopher, Philip; Hommy Dorthy Ellyany Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study examines the influence of Green Marketing strategies and Brand Image on Customer Loyalty among Unilever consumers in the Sekip subdistrict of Medan, Indonesia. As climate change and environmental issues increasingly shape consumer preferences, green marketing has become a vital strategy for brands globally. This research adopts a quantitative approach, utilizing a structured questionnaire to collect insights from Unilever consumers who prioritize eco-friendly products and corporate social responsibility. Results reveal that both Green Marketing and Brand Image significantly affect Customer Loyalty, though the impact may be slightly negative if perceived as insincere. Consumers are more loyal to brands that genuinely integrate sustainable practices, as seen in increased loyalty and sales for Unilever’s Sustainable Living Brands in Medan. However, Green Marketing and Brand Image explain only 13.1% of the variance in Customer Loyalty, with the remaining 86.9% influenced by other factors. These findings offer valuable insights for companies seeking to develop sustainable marketing strategies that resonate with environmentally aware consumers.